A comprehensive micromechanical modeling of electro-thermo-mechanical behaviors of CNT reinforced smart nanocomposites. (15th May 2017) - Mahmoodi, M.J.; Vakilifard, M.
Abstract: Electro-thermo-elastic properties of CNT reinforced smart nanocomposites are predicted by a micromechanical method newly developed for piezoelectric and dielectric effects in the present study. The CNT is replaced by an effective rigorous carbon fiber and interphase demonstrating the van der Waals interactions. The CNTs regular and random arrangement within the matrix are taken into account. CNT reinforced PVDF (CNTRPVDF) nanocomposite is considered. Validation of the presented method is carried out by available experimental and theoretical studies. The effects of interphase thickness and Young's modulus, CNT volume fraction (CNTVF), orientation and aspect ratio on the effective properties of CNTRPVDF are examined. Results show that difference between random and square packing are negligible for the thermo-elastic properties while the difference is more pronounced for the piezoelectric properties. It is found that interphase region has a significant influence on the effective properties. Whereas, its influence on longitudinal properties is much greater than transverse properties. The orientation of CNTs plays an important role in the effective properties. An optimum CNT angle for maximum value of any property is reported. The results also state that the short CNTs with aspect ratios more than 100 can be treated as long CNTs for most of the properties. Graphical abstract: Highlights: Electro-thermo-elastic properties of CNT reinforced piezo-polymeric smart nanocomposites are predicted by a micromechanical method and validated by experimental data. The effects of interphase thickness, interphase Young's modulus, CNT volume fraction, orientation and aspect ratio on the effective longitudinal and shear moduli, Poisson's ratio, coefficient of thermal expansion, dielectric and piezoelectric properties of CNT reinforced polyvinylidene fluoride (PVDF) are studied in both of the CNT square regular and random arrangement within the matrix. In the studied smart nanocomposite system, the difference between the square packing and random distribution are negligible for thermo-elastic properties, while the difference is more pronounced for piezoelectric properties due to the PVDF polarization direction. An optimum CNT orientation angle to obtain maximum value for any properties is reported. Short CNTs with aspect ratios more than 100 can be treated as long CNTs and one can use the related long CNT reinforced NCs theories.